The Mechanism Underlying the Influence of Indole-3-Propionic Acid: A Relevance to Metabolic Disorders - Zhang, Binbin; Jiang, Minjie; Zhao, Jianan; Song, Yu; Du, Weidong; Shi, Junping (Frontiers in Endocrinology, 2022)
The increasing prevalence of metabolic syndrome has become a serious public health problem. Certain bacteria-derived metabolites play a key role in maintaining human health by regulating the host metabolism. Recent evidence shows that indole-3-propionic acid content can be used to predict the occurrence and development of metabolic diseases. Supplementing indole-3-propionic acid can effectively improve metabolic disorders and is considered a promising metabolite. Therefore, this article systematically reviews the latest research on indole-3-propionic acid and elaborates its source of metabolism and its association with metabolic diseases. Indole-3-propionic acid can improve blood glucose and increase insulin sensitivity, inhibit liver lipid synthesis and inflammatory factors, correct intestinal microbial disorders, maintain the intestinal barrier, and suppress the intestinal immune response. The study off the mechanism of the metabolic benefits of indole-3-propionic acid is expected to be a potential compound for treating metabolic syndrome.